Trigger warnings, the organic classroom, and civil discourse. Issue 2 (2nd July 2016) - Thorpe, M. Elizabeth
Abstract: In this article I respond to my fellow contributors' thoughts on trigger warnings, and expand the conversation in terms of trigger warnings' effect on pedagogy and practice in the classroom. I parse out some definitions that make the debate difficult to negotiate, separate TWs from microaggressions, and apply this analysis to the dialogic classroom. I call for a civil discussion on this controversial topic, and challenge colleagues from all reaches of the ideological spectrum to approach the topic with respect for each other.